Preparation method of lithium metal lithium-free negative electrode

By using porous aluminum foil material in lithium metal batteries and forming a lithium aluminum alloy layer through electrochemical reactions, the problems of lithium dendrites growth and interface instability are solved, and the cycle stability and life of lithium metal batteries are significantly improved.

CN119786539AActive Publication Date: 2025-04-08HUBEI NANGUI ALUMINUM GRP CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411893564.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

During the circulation process of lithium metal batteries, there is uncontrollable growth of lithium dendrites and unstable interfaces, and the reactivity of lithium metal with electrolyte is high, resulting in a degradation of circulation performance.

Method used

The porous aluminum foil material is used as the negative electrode, and the surface lithium aluminum alloy layer is activated by lithiation/delithation electrochemical reaction to protect the matrix aluminum, thereby enhancing the cyclic stability of the electrode.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, enhance the cycle stability during charging and discharging, and improve the Coulomb efficiency and cycle life of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786539A_ABST
    Figure CN119786539A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a lithium metal lithium-free negative electrode, a porous aluminum foil has excellent electrolyte wettability and relatively high specific surface area, and is beneficial to improving the transmission efficiency of lithium ions and electrons, so that the lithium storage activity is improved. Meanwhile, the invention further provides an electrochemical reconstruction method of the aluminum negative electrode, and a special lithium-aluminum alloy layer is formed on the surface of the aluminum negative electrode through alloying reaction; by adjusting electrochemical reaction conditions, the form and microstructure of the lithium-aluminum alloy are optimized, so that the non-uniform deposition of lithium metal when the lithium-aluminum alloy is used as a lithium-free negative electrode of a lithium metal battery is inhibited. Results show that the lithium metal battery lithium-aluminum negative electrode provided by the invention is obviously superior to traditional aluminum foil, commercial porous aluminum foil and non-activated self-made porous aluminum foil in the aspects of cycling stability and safety. The method has important application value in the technical field of lithium metal batteries, and an effective solution can be provided for development and commercialization of high-energy-density lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation of a lithium metal lithium-free negative electrode, and specifically relates to the technical field of porous aluminum foil material preparation, which is used for a lithium metal lithium-free negative electrode and belongs to the technical field of lithium metal battery manufacturing. Background Art

[0002] Lithium metal batteries use lithium as the negative electrode. Compared with lithium-ion batteries, they have higher theoretical specific capacity and output voltage (redox potential -3.040 V), reflecting broad development prospects and competitive advantages. However, during the cycle process, the metal lithium negative electrode still has the following problems to be solved. First, during the charge and discharge process, the lithium dendrites formed by the uneven deposition-dissolution of lithium metal have uncontrollable growth and interface instability; second, lithium metal has high reaction activity with the electrolyte and is prone to side reactions, resulting in a decrease in cycle performance. To solve the above problems, researchers optimized the negative electrode materials of lithium metal batteries from the aspects of the composition and structural design of the current collector, surface protection, etc., in order to improve the electrochemical cycle stability and safety of lithium metal batteries.

[0003] From the perspective of the selection of negative electrode materials for lithium metal batteries, electrochemically inert metals such as copper have been widely studied. On the one hand, copper has good conductivity and electrochemical stability, which is conducive to the uniform deposition / stripping of lithium metal and has a certain stability. However, the deposition process often shows a large polarization, indicating poor reaction kinetics and unsatisfactory cycle performance under high current. On the other hand, the processing technology of copper foil is mature, which is conducive to its large-scale application and industrialization, and significantly reduces costs. At the same time, by modifying the copper surface with active metal elements that can form alloys with lithium, the lithium deposition overpotential can be significantly reduced, and its deposition / stripping reaction kinetics can be further improved, thereby significantly improving its performance. By rationally utilizing the stability of electrochemically inert metals and the rapid lithiation reaction kinetics of electrochemically active metal elements, it is expected to develop high-performance lithium metal lithium-free negative electrode materials.

[0004] Aluminum is a traditional metal material with abundant reserves, low cost and mature processing technology. It is not only widely used in traditional fields such as construction, decoration, vehicles, military, aerospace, etc., but also has great application prospects in the emerging field of new energy batteries. As a positive electrode of lithium-ion batteries and a positive and negative electrode current collector of sodium-ion batteries, it has a more obvious cost advantage than copper. However, aluminum itself is also a high-capacity negative electrode material for lithium-ion batteries, which can react with lithium to form an alloy. As a negative electrode of a lithium metal battery, it will cause structural pulverization due to reaction with lithium, resulting in serious performance degradation. Therefore, so far, there have been few reports on high-performance aluminum negative electrodes for lithium metal batteries. This patent aims to make full use of the cost advantage of aluminum, overcome the deficiency of structural damage caused by its reaction with lithium through electrochemical means, and then develop a type of high-performance aluminum negative electrode for lithium metal batteries.

[0005] To this end, this patent has developed a preparation process for porous aluminum foil. On the one hand, compared with traditional aluminum powder materials, the exposed surface area of ​​porous aluminum foil is reduced, which can minimize the surface oxide layer and improve the reaction activity of the material; on the other hand, the porous structure can effectively enhance the contact between the material and the electrolyte and improve the reaction kinetics while effectively enhancing the structural stability of the material in the electrochemical reaction. On this basis, by optimizing the electrochemical reaction parameters, a lithium-aluminum alloy protective layer with a special structure is generated on the surface of the active aluminum, which maintains the stable deposition / stripping reaction of the lithium metal while playing a good protective role on the aluminum matrix. The prepared porous aluminum foil is a new type of lithium metal battery negative electrode formed by electrochemical reconstruction, which has excellent electrochemical properties and reflects great research value and application potential. Summary of the invention

[0006] The present invention proposes a novel method for preparing a negative electrode for a lithium metal battery, assembling a battery using the prepared porous aluminum foil, and forming a surface lithium aluminum alloy layer through lithiation / delithiation electrochemical reaction activation to protect the matrix aluminum, thereby improving the cycle stability of the electrode as a negative electrode for a lithium metal battery. Through electrochemical activation, the morphology and microstructure of the lithium aluminum alloy surface layer can be effectively regulated, further activating the active sites on the surface, thereby achieving a more uniform lithium deposition / stripping reaction. At the same time, the activation process can also promote the formation and stabilization of the SEI film, reduce the irreversible consumption and capacity attenuation of lithium in subsequent charging and discharging processes, thereby effectively improving the coulombic efficiency and cycle life of the lithium metal battery. The design method of the aluminum negative electrode provided by this patent is expected to provide new ideas and solutions for the commercial application of lithium metal batteries.

[0007] Technical Solution The technical solution of the present invention comprises the following steps: (1) First, a certain amount of polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) were weighed and added to N,N-dimethylformamide (DMF) and stirred for a period of time (including heating in a 50 °C water bath for 5 h) to obtain a colorless transparent solution, which was referred to as solution A. (2) Directly take a certain amount of ethylene glycol as solution B; (3) preparing nanofibers by electrospinning solution A, and spraying solution B by electrostatic spraying to form a carbon nanofiber membrane and deposit it on aluminum foil, thereby obtaining a precursor carbon nanofiber membrane / aluminum foil composite; (4) drying (3) in an air drying oven to remove the solvent; (5) Sintering (4) in an air atmosphere for a period of time, and then heat treating it under Ar / H2 gas protection, so that the high molecular polymer is decomposed or carbonized, and the aluminum foil is melted and flows along the surface of the carbon material to form a porous aluminum structure.

[0008] (6) A button battery is assembled using a porous aluminum foil material as the negative electrode and a metal lithium sheet as the positive electrode, and electrochemical alloying is performed to obtain a Li-Al alloy, which is a lithium metal-free lithium negative electrode.

[0009] Preferably, in step (1), the mass ratio of polyacrylonitrile (PAN) to polyvinyl pyrrolidone (PVP) is 0.3-0.6 g: 0.1-0.2 g; Preferably, the stirring time in step (1) is 30-48 h; Preferably, in step (2), the amount of ethylene glycol is 2-5 mL; Preferably, the conditions for electrospinning combined with electrostatic spraying in step (3) are: temperature of 40-60°C, humidity of 20-30%, voltage of 15-20 kV, receiving distance of 15-25 cm, and electrospinning / spraying for 8-15 hours; Preferably, in step (4), the drying temperature is 50°C-80°C, and the drying time is 18-24 h; Preferably, in step (5), the sintering temperature in air atmosphere is 200-300°C, and the sintering time is 2-5 h; Preferably, in step (5), the heat treatment temperature under Ar / H2 gas protection is 650-750°C and the time is 2-5 h; Preferably, during the battery test, the first three cycles are activated by controlling the current density and the battery capacity, so that the lithium ions can be effectively embedded in the structure of the porous aluminum foil to form a Li-Al alloy, thereby further improving the electrochemical performance of the battery; Preferably, during the activation process, the charge and discharge current density is 0.01-0.05 A g -1 , and the discharge capacity is 50-200 mAh g each time -1 to ensure that lithium ions can form a surface alloy layer with porous aluminum in an appropriate amount and maintain the structural integrity of the porous aluminum.

[0010] Compared with the prior art, the advantages and beneficial effects of the present invention are: (1) Significant cost-effectiveness: Aluminum, as an increasingly widely used cheap metal material, has better cost advantages than traditional copper negative electrodes, which helps to reduce the production cost of lithium metal batteries.

[0011] (2) Enhanced interface stability: Using a specific lithium-aluminum alloy layer as the protective layer of the aluminum negative electrode can effectively improve the interface stability between the aluminum matrix and the lithium metal, reduce the structural powdering phenomenon caused by the reaction, and extend the battery life.

[0012] (3) Excellent electron and ion transport: The design of porous aluminum foil provides a higher specific surface area and good electrolyte wettability, which helps to improve the transmission efficiency of lithium ions and electrons, thereby enhancing lithium storage activity.

[0013] (4) Improved cycle stability: The present invention effectively inhibits the growth of lithium dendrites and enhances the cycle stability during the charge and discharge process by designing a porous structure in the aluminum-based material and combining it with a special electrochemical reconstruction method.

[0014] (5) Environmentally friendly: Using porous aluminum foil as the negative electrode material has lower environmental impact and better sustainability compared to other heavy metal or environmentally friendly negative electrode materials, and meets the requirements of modern environmental protection.

[0015] (6) Effective electrochemical protection: The lithium-aluminum alloy layer formed by electrochemical reconstruction not only makes the lithium deposition and stripping reactions more stable, but also protects the aluminum-based negative electrode material and prevents its performance degradation caused by reaction with lithium. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present invention will be further described below in conjunction with the accompanying drawings.

[0017] Figure 1 Optical photograph of the sample precursor prepared in Example 1.

[0018] Figure 2 Optical photographs of the samples prepared in Example 1: (a) optical photograph of the carbon nanofiber membrane; (b) optical photograph of the porous aluminum foil.

[0019] Figure 3 XRD of the porous aluminum foil prepared in Example 1.

[0020] Figure 4 SEM images of the materials prepared in Example 1: (a) SEM image of carbon nanofiber membrane; (bc) SEM image of porous aluminum foil.

[0021] Figure 5 Contact angle test pictures of Examples 1, 3 and 4.

[0022] Figure 6 Electrochemical performance diagrams of Example 1: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0023] Figure 7 Electrochemical performance diagrams of Example 2: (a) charge and discharge curves of the first three cycles; (b) charge and discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0024] Figure 8Electrochemical performance diagrams of Example 3: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0025] Fig. 9 Electrochemical performance diagrams of Example 4: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0026] Fig.10 Electrochemical performance diagrams of Example 5: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0027] Fig.11 Electrochemical performance diagrams of Example 6: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0028] Fig.12 Electrochemical performance diagrams of Example 7: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0029] Fig.13 Electrochemical performance diagrams of Example 8: (a) charge-discharge curves of the first three activation cycles; (b) charge-discharge curves of the 4th to 6th cycles; (c) cycle efficiency diagram.

[0030] Fig.14 Time-voltage curve diagram of Example 1. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the following embodiments will further illustrate the present invention in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. On the contrary, the present invention covers any substitutions, modifications, equivalent methods and schemes made on the essence and scope of the present invention as defined by the claims. Further, in order to enable the public to have a better understanding of the present invention, some specific details are described in detail in the following detailed description of the present invention. For those skilled in the art, the present invention can be fully understood without the description of these details.

[0032] The present invention adopts electrostatic spinning combined with electrostatic spraying to prepare porous aluminum foil, which has a larger specific surface area and good electrolyte wettability compared with ordinary aluminum foil. The preparation process of the present invention is green and environmentally friendly, the reaction process is controllable, the process is simple, the preparation cycle is short, and the cost is low. The surface lithium aluminum alloy layer is activated by the first three cycles of lithiation / delithiation electrochemical reaction to protect the matrix aluminum, thereby improving the cycle stability of the electrode as the negative electrode of the lithium metal battery. Through the first three cycles of electrochemical activation, the morphology and microstructure of the lithium aluminum alloy surface layer can be effectively regulated, and the active sites on the surface can be further activated, thereby achieving a more uniform lithium deposition / stripping reaction. At the same time, the activation process can also promote the formation and stabilization of the SEI film, reduce the irreversible consumption and capacity decay of lithium in the subsequent charging and discharging process, thereby effectively improving the coulombic efficiency and cycle life of the lithium metal battery. The design method of the aluminum negative electrode provided by this patent is expected to provide new ideas and solutions for the commercial application of lithium metal batteries.

[0033] Example 1 First, weigh 0.45 g polyacrylonitrile (PAN) and 0.15 g polyvinyl pyrrolidone (PVP) and add them to 4.56 mL N,N-dimethylformamide (DMF) and stir for 48 h (including heating in a 50°C water bath for 5 h) to obtain a colorless transparent solution as solution A. Directly take 2.5 mL of ethylene glycol as solution B.

[0034] Solution A was transferred into a syringe with a nozzle diameter of 0.33 mm and a capacity of 5 mL, and solution B was transferred into a syringe with a nozzle diameter of 0.33 mm and a capacity of 2.5 mL. The aluminum current collector was used as the receiving end for double needle blending. The positive voltage was 15 kV, the negative voltage was 3 kV, the temperature was 45 °C, the humidity was 30 ± 5%, the receiving distance was 15 cm, and the injection rate was 0.42 mL h -1 The collected products were dried in an oven at 60 °C for 20 h to obtain a precursor nanofiber membrane / aluminum foil composite ( Figure 1 ).

[0035] Then, the precursor nanofiber membrane / aluminum foil composite was heated at 1°C min in air. -1 The pre-oxidation was carried out at 250 °C for 3 h and then heated at 5 °C min-1 in an argon atmosphere. -1 The carbon nanofiber membrane and porous aluminum foil material ( Figure 2 The sintered material was analyzed by XRD, and the obtained diffraction peaks corresponded well to Al (PDF#85-1327) ( Figure 3 The obtained samples were tested by scanning electron microscope (SEM). Figure 4As shown in a, the material presents a fibrous morphology. Figure 4 As shown in b, the prepared porous aluminum foil exhibits an obviously rough and irregular morphology.

[0036] The materials were made into batteries as follows: porous aluminum foil was used as the negative electrode / counter electrode, Celgard 2400 microporous polypropylene was used as the separator, 1M LiTFSI was dissolved in DME+DOL (volume ratio of 1:1) solution and 2% LiNO3 additive was used as the electrolyte, and metal lithium sheets were assembled into CR2025 button batteries in an argon-protected glove box. After all the batteries were assembled, they were left to stand for 8 hours and then the electrochemical performance was tested using the LAND CT2001A battery test system.

[0037] First, the current density and battery capacity were controlled in the first three cycles for activation (the current density was 0.03 A g -1 , with a capacity of 100 mAh g -1 ), so that lithium ions can effectively react with the porous aluminum foil to form a Li-Al alloy. This ensures that lithium ions can form a surface alloy layer with the porous aluminum in an appropriate amount and maintain the structural integrity of the porous aluminum. Then, at a current density of 0.2 A g -1 , with a capacity of 600 mAh g -1 The cycle performance test was carried out under the conditions of

[0038] Example 2 This embodiment only changes the test method in embodiment 1, and only does not perform the first three activation cycles, and directly conducts the test at a current density of 0.2 A g -1 , with a capacity of 600 mAh g -1 The electrochemical performance tests were carried out under the conditions of .

[0039] Example 3 In this embodiment, the porous aluminum foil used for assembling the battery in Example 1 is only replaced with a commercial porous aluminum foil (Desco Electronic Technology (Kunshan) Co., Ltd.), which is not further processed and is directly sliced ​​to assemble the battery. The battery assembly and testing methods are exactly the same as in Example 1.

[0040] Example 4 In this embodiment, the porous aluminum foil used for assembling the battery in Embodiment 1 is only replaced with a commercial current collector aluminum foil, which is not further processed and is directly sliced ​​to assemble the battery. The battery assembly and testing methods are exactly the same as those in Embodiment 1.

[0041] Example 5 In this example, the electrolyte used for assembling the battery in Example 1 was only changed to an electrolyte of EC+DMC+DEC (volume ratio of 1:1:1) solution containing LiPF6 (1 mmol / L), and the test method was exactly the same as that in Example 1.

[0042] Example 6 In this embodiment, the porous aluminum foil used for assembling the battery in Embodiment 1 is only replaced with commercial copper foil, which is not further processed and directly sliced ​​and assembled into batteries. The battery assembly and testing methods are exactly the same as those in Embodiment 1.

[0043] Example 7 This embodiment only changes the test method in embodiment 1, and only changes the current density during the alloying process to 0.01A g -1 , capacity changed to 200 mAh g -1 After alloying, the current density is still 0.2 A g -1 , with a capacity of 600 mAh g -1 The electrochemical performance tests were carried out under the conditions of .

[0044] Example 8 This embodiment only changes the test method in embodiment 1, and only changes the current density during the alloying process to 0.05A g -1 , capacity changed to 200 mAh g -1 After alloying, the current density is still 0.2 A g -1 , with a capacity of 600 mAh g -1 The electrochemical performance tests were carried out under the conditions of .

[0045] The contact angle test was conducted on Example 1, Example 3 and Example 4. The prepared porous aluminum foil was cleaned and a certain volume of electrolyte was dripped onto the surface of the porous aluminum foil using a micropipette. After the droplet was stable, the contact angle measuring instrument Theta Lite was used to take an image of the droplet and the contact angle was automatically measured by the software analysis system. The analysis results are shown in Table 1. Figure 5 As shown, the porous aluminum foil prepared by Example 1 can reduce the contact angle of the electrolyte from 43.54° to about 25.95° (and less than the contact angle of 32.37° of the commercial porous aluminum foil), indicating that the surface energy of the porous aluminum foil is increased and the surface roughness may also be increased, thereby improving the wettability of the electrolyte.

[0046] Electrochemical performance analysis: Electrochemical performance tests were performed using the LAND CT2001A battery testing system. Figure 6a, 8a, 9a, 10a, 11a, 12a and 13a are charge and discharge curves of the first three activation cycles of the assembled batteries in the examples, wherein the current density of examples 1, 3, 4, 5 and 6 is 0.03 A g -1 , with a capacity of 100 mAh g -1 , while the current densities of Examples 7 and 8 were 0.01 A g -1 and 0.05A g -1 , the capacity is 200 mAh g -1 , the horizontal axis represents the mass capacity, and the vertical axis represents the voltage. The porous aluminum foil prepared in Example 1 has a significantly improved initial efficiency compared to the commercial porous aluminum foil in Example 3 and the aluminum current collector in Example 4. The commercial copper foil in Example 6 has a high initial efficiency, but the efficiency gradually deteriorates as the charge and discharge proceed. This may be because the repeated deposition / stripping process during the charge and discharge process causes the lithium metal to form an uneven crystal structure on the surface of the copper foil, which in turn affects the battery cycle stability. Compared with the alloying process in Example 1, the reaction in Example 7 proceeds faster. There is basically no difference between the alloying process in Example 8 and Example 1. Appendix Figure 7 a is the case in Example 2 where the activation was not performed through the first three cycles and the current density was directly 0.2 A g -1 , with a capacity of 600 mAh g -1 The charge and discharge curves under the conditions of Figure 6 b-13b is an example in which the current density is 0.2 A g -1 , with a capacity of 600 mAh g -1 The 4th, 5th and 6th cycle curves of charge and discharge under the condition of , it can be seen from the figure that all the discharge curves are below 0 V in the later stage, which is obviously the lithium deposition behavior. Figure 6 As shown in c-13c, the horizontal axis represents the number of cycles, and the vertical axis represents the coulombic efficiency. The results show that the porous aluminum foil is used as the negative electrode material, 1 M LiTFSI is dissolved in a DME+DOL (volume ratio of 1:1) solution and 2% LiNO3 additive as the electrolyte, and the battery after activation can effectively realize the alloying reaction between lithium ions and the porous aluminum foil to form a Li-Al alloy. This Li-Al alloy can not only be further used as the negative electrode layer of the lithium metal battery, but also provide good protection for the substrate aluminum layer during the deposition and stripping of lithium, thereby significantly improving the cycle stability and life of the battery. At a current density of 0.2 A g -1 Mass capacity is 600 mAh g -1 Under the conditions, it can stably cycle more than 300 times and the cycle time is more than 2000 hours (such as Fig.14 as shown).

[0047] In Example 2, the commercial aluminum foil was not activated and deactivated after 80 cycles. In Example 3, the commercial aluminum foil began to decay after about 80 cycles. In Example 4, the aluminum current collector began to decay after about 45 cycles. In Example 5, the LiPF6 electrolyte was used and deactivated after 130 cycles. In Example 6, the commercial copper foil was deactivated after about 103 cycles. In Example 7, the current density during the alloying process was changed to 0.01 A g -1 , capacity changed to 200 mAh g -1 After 170 cycles, the current density began to decay. Example 8: The current density during the alloying process was changed to 0.05 A g -1 , capacity changed to 200 mAh g -1 In summary, porous aluminum foil was used as the negative electrode material, 1 M LiTFSI was dissolved in DME+DOL (volume ratio of 1:1) solution and 2% LiNO3 additive as the electrolyte, and the current density was 0.03 A g -1 , with a capacity of 100 mAh g -1 The activated battery has a stable and long cycle life of up to 2000 h.

Claims

1. A method for preparing a lithium metal-free lithium negative electrode, characterized in that: During the charge and discharge process, an alloying reaction occurs to form a Li-Al alloy layer, thereby forming a lithium metal negative electrode. The preparation method of a lithium metal-free lithium negative electrode comprises the following steps: (1) First, weigh polyacrylonitrile PAN and polyvinyl pyrrolidone PVP, add them into N,N-dimethylformamide DMF and stir to obtain a colorless transparent solution, which is solution A; (2) Ethylene glycol as solution B; (3) preparing nanofibers by electrospinning solution A, and spraying solution B by electrostatic spraying to form a carbon nanofiber membrane and deposit it on aluminum foil, thereby obtaining a precursor carbon nanofiber membrane / aluminum foil composite; (4) drying and pre-sintering the precursor carbon nanofiber membrane / aluminum foil composite of (3), and then heat treating the composite to obtain a porous aluminum foil material; (5) A button battery is assembled using a porous aluminum foil material as the negative electrode and a metal lithium sheet as the positive electrode, and electrochemical alloying is performed to obtain a Li-Al alloy, which is a lithium metal-free lithium negative electrode.

2. The method for preparing a lithium metal lithium-free negative electrode according to claim 1, characterized in that: The mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is 3-6:1-2.

3. The method for preparing a lithium metal lithium-free negative electrode according to claim 1, characterized in that: The conditions for electrospinning combined with electrostatic spraying are: temperature of 40-60°C, humidity of 20-30%, voltage of 15-20 kV, and receiving distance of 15-25 cm, and electrospinning / spraying for 8-15 hours.

4. The method for preparing a lithium metal lithium-free negative electrode according to claim 1, characterized in that: The pre-sintering conditions in step (4) are as follows: the sintering temperature is 200-300°C in an air atmosphere, and the sintering time is 2-5 h.

5. The method for preparing a lithium metal lithium-free negative electrode according to claim 1, characterized in that: The heat treatment conditions in step (4) are as follows: the heat treatment temperature is 650-750°C and the time is 2-5 h under Ar / H2 gas protection.

6. The method for preparing a lithium metal lithium-free negative electrode according to claim 1, characterized in that: During the electrochemical activation process, the charge and discharge current density is 0.01-0.05 A g -1 , discharge capacity is 50-200 mAh g -1 .

7. The method for preparing a lithium metal lithium-free negative electrode according to claim 6, characterized in that: The electrochemical activation treatment is a 3-5 cycle activation process.

8. A negative electrode material for a lithium-ion battery, comprising a lithium metal-free negative electrode obtained by the method according to any one of claims 1 to 7.

9. A battery material, comprising a lithium metal-free lithium negative electrode obtained by the method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Porous composite negative electrode material of lithium ion battery and preparation method thereof

    CN106941167A

  • Multi-layer electrode structure for lithium sulfur battery and preparation method thereof

    CN108630890A

  • 3D anode composite material and preparation method and application thereof

    CN116454234A

  • Preparation method of aluminum-based negative electrode material of lithium ion battery

    CN118213496A

  • Preparation method and application of self-supporting three-dimensional carbon fiber embedded elemental aluminum composite material

    CN118538889A